IMPLEMENTATION OF FACE-TO-FACE LEARNING AFTER ONLINE LEARNING AND LIMITED FACE-TO-FACE LEARNING IN SOCIOLOGY LEARNING - Utami, Farhana Atmayani; Astutik, Dwi; Nurhadi, Nurhadi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2023)
Implementing face-to-face learning after online and face-to-face learning is limited to causing obstacles when learning sociology. This study aims to describe the implementation of face-to-face learning after online and face-to-face learning is limited to sociology learning at SMA Negeri 1 Kartasura. The type of research used in research is descriptive qualitative with a case study approach. The results of this study show that the implementation of face-to-face learning after online and face-to-face learning is limited to three stages. The three stages are the preparation stage, the implementation stage, and the evaluation stage. The three stages are then analyzed using the perspective of Functional Structural theory with four prerequisites: Adaptation, Goal Attainment, Integration, and Latency. Based on the theory analysis, each figure has its own role in learning sociology. Implementation of learning, face-to-face learning, and sociology learning.